Preparation of PEO/Clay Nanocomposites Using Organoclay Produced via Micellar Adsorption of CTAB - Ahmet Gürses; Mehtap Ejder-Korucu; Çetin Doğar (The Scientific World Journal)
The aim of this study was the preparation of polyethylene oxide (PEO)/clay nanocomposites using organoclay produced via micellar adsorption of cethyltrimethyl ammonium bromide (CTAB) and their characterisation by X-ray diffraction (XRD), and Fourier transform infrared (FT-IR) spectra, and the investigation of certain mechanical properties of the composites. The results show that the basal distance between the layers increased with the increasing CTAB/clay ratio as parallel with the zeta potential values of particles. By considering the aggregation number of CTAB micelles and interlayer distances of organo-clay, it could be suggested that the predominant micelle geometry at lower CTAB/clay ratios is an ellipsoidal oblate, whereas, at higher CTAB/clay ratios, sphere-ellipsoid transition occurs. The increasing tendency of the exfoliation degree with an increase in clay content may be attributed to easier diffusion of PEO chains to interlayer regions. FT-IR spectra show that the intensity of Si-O stretching vibrations of the organoclays (1050 cm−1) increased, especially in the ratios of 1.0 g/g clay and 1.5 g/g clay with the increasing CTAB content. It was observed that the mechanical properties of the composites are dependent on both the CTAB/clay ratios and clay content of the composites.